THE PLATELET-TO-LYMPHOCYTE RATIO ON ACUTE COMPLICATION OF DIABETES MELLITUS - Hariogie Putradi; Catur Suci Sutrisnani (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Hariogie Putradi1, Catur Suci Sutrisnani2 BSTRACT Hyperglycemia crisis can occur in Diabetes Mellitus (DM). The uncontrolled complications of DM are Diabetic Ketoacidosis (DKA) and Hyperglycemic Hyperosmolar State (HHS). Inflammatory response is potentially occur in these condition. Platelet-to-Lymphocyte Ratio (PLR) is a new marker of inflammation in which platelet counts tend to increase, while lymphocyte counts tend to decrease due to severe apoptosis. Describe PLR on acute complication of DM and to know the difference of PLR between DKA and non-DKA (HHS and Mixed). Retrospective study in patients with acute complication of DM in dr. Saiful Anwar General Hospital Malang in January 2017-May 2018. The platelet and lymphocyte count were obtained from the Laboratory Information System (LIS). The PLR was calculated by dividing the platelet count by the lymphocyte count. A total of 71 patients were involved in the study, consisting of 21 DKA patients and 50 non-DKA patients. There was significant difference of platelet count between DKA and non-DKA patients (p=0,001). However, there were no significant differences of lymphocyte count (p=0,087) and PLR (p=0,762) between DKA and non-DKA patients. In DKA, there is a chronic inflammatory process that can affect PLR. As a result, platelet counts tend to increase, while lymphocyte counts tend to decrease due to severe apoptosis. The study showed significant difference of platelet count between DKA and non-DKA groups, and no significant difference of PLR between DKA and non-DKA groups. It is recommended to conduct further research with larger sample size.